Metal Nanoparticles for Drug Delivery and Diagnostic Applications - Shah, Muhammad Raza (Micro and Nano Technologies Ser., 2019)
Metal Nanoparticles for Drug Delivery and Diagnostic Applications addresses the lifecycle of metal nanoparticles, from synthesis and characterization, to applications in drug delivery and targeting. It is an important resource for those in biomaterials, nanomedicine and pharmaceutical sciences, exploring gold, silver and iron-based drug delivery systems for controlled and targeted delivery of potential drugs and genes for enhanced clinical efficacy. Nanotechnology is widely used in drug delivery due to its ability to reduce plasma fluctuation of drugs, high solubility, and efficiency, the relatively low cost of nanoscale products, and enhancement of patient comfort, hence this resource is a welcome edition to the science.